Sur les traces de Tupaia entre Tahiti, Ra’iātea et Nouvelle-Zélande. L’héritage de la navigation ‘traditionnelle’ - Francesco Lattanzi (Archivio Antropologico Mediterraneo)
This article is part of a rich framework of theoretical reflection on the seas and the oceans, and proposes an itinerary of anthropology of the seas between the Mediterranean Sea and the Pacific Ocean, to explore nautical experiences different from those developed in the West. I will discuss the contemporary imaginary of the ‘traditional’ navigation heritage in French Polynesia, starting from the TUIA-Encounters 250 commemorations, organized in New Zealand to celebrate both the 250th anniversary of James Cook’s – Captain of the British Navy – arrival from Tahiti and the tradition of transpacific voyages in a wider sense, following a process of decolonization of the event. The text’s purpose is to reconsider/revive this navigation heritage, which is metaphorically represented by the articulated return of Tupaia’s memory, the expert navigator and ritual operator originating from Ra’iātea, famous for having joined the crew of James Cook’s ship on his trip from Tahiti to Aotearoa.